Good practices for the meat industry. - Jutzi, Samuel (FAO animal production and health manual, 2004)
In recent years, public concern about the safety of foods of animal origin has heightened due to problems that have arisen with bovine spongiform encephalopathy (BSE), as well as with outbreaks of food-borne bacterial infections, and food contamination with toxic agents (e.g. dioxin). These problems have serious implications for national food safety, the development of the animal products industry, and for international trade in livestock products. Accordingly, the FAO/WHO Codex Alimentarius Commission is in the final stages of negotiation of a new Code of hygienic practice for meat. The Code implies a transition from meat inspection towards a risk-based approach covering the entire food chain. The Manual on good practices for the meat industry aims to assist the industry to prepare itself for compliance with the new regulatory framework, which is expected to come into force when the Code is approved in 2005. It is targeted at the meat industry in developing countries and in emerging economies in their endeavour to meet the rising quality and safety requirements both of the export industry and domestic markets, with the increased participation of large-scale retailers. The publication is intended to guide managers of abattoirs and the meat industry. The Codex Alimentarius "Draft code of hygienic practice for meat" is included as an appendix.